PERAN ASURANSI PERLINDUNGAN TENAGA KERJA INDONESIA DALAM PEMUTUSAN HUBUNGAN KERJA TENAGA KERJA INDONESIA DI LUAR NEGERI - , VIEN ERLIANIES ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesian worker, hereinafter referred as TKI, is every Indonesian citizen who is qualified to work abroad in an employment relation for a certain period of time and receive wages. The Termination of Employment (PHK) becomes one of issues often experienced by TKI in working abroad